2021
DOI: 10.1155/2021/5250512
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Security and International Settlement System of Electronic Economy Based on Blockchain

Abstract: In recent years, the rapid development of e-commerce and mobile communications has ushered in a new era in the era of big data and has also given birth to emerging industries such as big data. People are paying more and more attention to data, and all walks of life are trying to analyze data and make use of the potential value of data. Business organizations use big data analysis to reduce business costs, plan real-time traffic routes for thousands of express vehicles to avoid congestion, and use click stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The research also indicated that enhancing transparency and incorporating sustainability factors into ECA activities were crucial to more comprehensively exposing these risks and creating a more sustainable growth environment for developing countries at the lower-tier level under the umbrella of international economic law. Liu et al [7] combined big data with e-commerce security to conduct in-depth research on the composition of ecommerce security systems and key security strategies and technologies. The analysis results showed that the proposed credential control system based on blockchain technology could effectively resist most fraudulent behaviors, ensuring secure storage and tamper-proofing of transaction data.…”
Section: Introductionmentioning
confidence: 99%
“…The research also indicated that enhancing transparency and incorporating sustainability factors into ECA activities were crucial to more comprehensively exposing these risks and creating a more sustainable growth environment for developing countries at the lower-tier level under the umbrella of international economic law. Liu et al [7] combined big data with e-commerce security to conduct in-depth research on the composition of ecommerce security systems and key security strategies and technologies. The analysis results showed that the proposed credential control system based on blockchain technology could effectively resist most fraudulent behaviors, ensuring secure storage and tamper-proofing of transaction data.…”
Section: Introductionmentioning
confidence: 99%